Chitosan Induces Plant Hormones and Defenses in Tomato Root Exudates - Suarez-Fernandez, Marta; Marhuenda-Egea, Frutos Carlos; Lopez-Moya, Federico; Arnao, Marino B.; Cabrera-Escribano, Francisca; Nueda, Maria Jose; Gunsé, Benet; Lopez-Llorca, Luis Vicente (Frontiers in Plant Science, 2020)
In this work, we use electrophysiological and metabolomic tools to determine the role of chitosan as plant defence elicitor in soil for preventing or manage root pests and diseases sustainably. Root exudates include a wide variety of molecules that plants and root microbiota use to communicate in the rhizosphere. Tomato plants were treated with chitosan. Root exudates from tomato plants were analysed at 3, 10, 20 and 30 days after planting (dap). We found, using High Performance Liquid Chromatography (HPLC) and Excitation Emission Matrix (EEM) fluorescence, that chitosan induces plant hormones, lipid signalling and defence compounds in tomato root exudates, including phenolics. High doses of chitosan induce membrane depolarization and affect membrane integrity. 1H-NMR showed the dynamic of exudation, detecting the largest number of signals in 20 dap root exudates. Root exudates from plants irrigated with chitosan inhibit ca. 2-fold growth kinetics of the tomato root parasitic fungus Fusarium oxysporum f. sp. radicis-lycopersici. and reduced ca. 1.5-fold egg hatching of the root-knot nematode Meloidogyne javanica.